Investigation of the Dispersion Behavior of Inertial Particles within Accelerated Domain - Tong ZHAO; Zhilong WANG; Masahiro TAKEI; Kai Liu; Yahui CUI (Journal of Applied Fluid Mechanics, 2015)
This report presents a study of the dynamics dispersion behaviors of inertial particle in solid-air two-phase flow within accelerated domains using both experimental and simulation approaches. In the simulation, a threedimensional model was proposed by means of the combined computational fluid dynamics and a discrete element method (CFD-DEM). The simulation model provides information regarding the particle distribution behaviors and the particle run-away rate from the calculation domain. In the experiment, particle image velocimetry (PIV) and laser tomography were used to measure the particle velocity and concentration distribution, respectively. The simulation results were than validated by the experimental measurement. And the influence mechanisms of acceleration on the particle flow behavior were discussed in detail. As results, acceleration of the calculation domain affects the particle motion and causes a relative dense particles distribution in the accelerated direction. The particle run-out rate under acceleration was initially the same, but subsequently lower than that of the condition without acceleration. This finding shows that the acceleration adversely affects the particle run-out rate.